An Infected Mediastinal Cyst - Lindsay M Lawson; Andrew C Mason (Canadian Respiratory Journal)
The authors describe a 43-year-old patient who had a mediastinal mass that became infected after a transbronchial needle aspirate biopsy. A paraspinal, extrapleural window with a saline-lidocaine mixture was created that allowed the placement of a percutaneous drainage catheter into the infected lesion. This procedure resulted in an excellent clinical outcome, and obviated the need for a thoracotomy and more invasive surgical management.